(untitled) - Kabala, Thomas (Albany, New York, 2000)
This book introduces to AC and DC generation and distribution of power, including three-phase power and transformers. Single-phase and three-phase generators are presented in detail, as well as transformers with various connections.
Keywords: Electric controllers,Electric machinery,Electric transformers; Direct current